FEASIBILITY STUDY OF MICRO HYDRO POWER PLANT CAPACITY IN BLUMBANG BANJARARUM KALIBAWANG KULONPROGO - Lintang Timur; Fifin Hindarti; Rosiana Indrawati (Master in Systems Engineering, 2020)
The Blumbang micro hydro power plant is a power plant utilizing hydropower that supplies electricity to the Blumbang area. The resulting supply is very large, around 30 kWh. However, it cannot be fully used by the surrounding society. So, it is necessary to do a feasibility study to increase the power capacity to determine supply and demand. This research aims to determine the community's supply and demand, which will impact the potential that can be taken by society.The method used is field observations, supply and demand observations, analysis of differences in supply and demand. The results that the feasibility of increasing the power capacity. It supplies generated from PLTMH Blumbang ranges from 24-26 kWh of the electricity demand of micro hydro power plant, 6 kWh demand electricity of micro hydro power plant and PLN 16 kWh. The Blumbang society's electricity bill has decreased with the Blumbang micro hydro power plant.